Pollution Based Study of Heavy Metals in Medicinal plants Aloe vera and Tamarix aphylla - Hamid Iqbal, Baharullah Khattak, Sultan Ayaz, Ali Rehman, Muhammad Ishfaq, Muhammad Naseer Abbas, Muhammad Saqib Malik, Abdul Wahab, Imran, Saifullah Mehsud (Journal of Applied Pharmaceutical Science, 2013)
The main objective of this study was to generate perception in community regarding pollution of heavy metals contained in Aloe vera and Tamarix aphylla plants which have wide range of medicinal use but having toxic concentration of heavy metals. The plant samples were collected at three different areas referred as spots i.e. polluted (spot 1), less polluted (spot 2) and non- polluted (spot 3) from District Kohat, Khyber Pakhtunkhwa, Pakistan. In the present study, essential heavy metals such as Cobalt (Co), Nickel (Ni), Chromium (Cr), Copper (Cu), Iron (Fe) and Zinc (Zn) and non-essential heavy metals Cadmium (Cd), Lead (Pb) were analyzed in Aloe vera leaves and Tamarix aphylla by using Flame atomic absorption spectrophotometer. Heavy metals concentration in different spots were found to be in order as Spot 1> Spot 2>Spot 3 with the concentration range of found heavy metals., Cd 0.25-0.51 mg/kg, Pb BDL-15.23, Co 1.90-3.31mg/kg, Ni 2.98-4.01 mg/kg, Cr 4.86-6.01 mg/kg, Cu 2.32-3.01 mg/kg, Fe 12.42-22.47 mg/kg, Zn 34.53-53.08 mg/kg for Aloe vera leaves and concentrations of the same heavy metals like Cd 0.13-0.31 mg/kg, Pb 1.00-18.01 mg/kg, Co 0.25-2.90 mg/kg , Ni 3.75-5.93 mg/kg , Cr 3.83-5.32 mg/kg , Cu 1.01-1.90 mg/kg, Fe 23.65-30.10 mg/kg , Zn 13.70-25.63 mg/kg were observed in the bark of Tamarix aphylla. Thus it was concluded from the present study that the samples collected from polluted area were found more contaminated with heavy metals as compared to less polluted and non-polluted area.
Keywords: Aloe vera, Tamarix aphylla, Heavy